Intermediate Space of Andriy Lyubka’s Novel “Your Look, Chio-Chio-san” - Kohut, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. In the modern Ukrainian scientific space, intermediality is widely developed in literary studies in various directions. The study of this phenomenon seems to be one of the most relevant and promising areas for musicology, which has a specific analytical toolkit that can reveal the deep meaning of the musical component of the text. Scientific novelty of research. The novel by the сontemporary Ukrainian author Andrei Lyubka “Your Look, Chio-Chio-san” for the first time becomes the object of musicological research and is considered in the context of intermediality. Main objective of the study – to consider the intermedial space of Andriy Lyubka’s novel “Your Look, Chio-Chio-san”, revealing in it different levels of connections of the verbal text with the opera by G. Puccini. Methodology. In the process of identifying literary and musical ties, an intermedia approach that is relevant in modern literary criticism and musicology was used; comparison of various parameters of the opera and the novel led to the use of the comparative method; to consider the musical component and its meaning in the verbal text, the method of intonation analysis was used. Results and conclusions. In A. Lyubka’s novel “Your Look, Chio-Chio-san” there are various channels of intersection of musical and verbal texts, presented through: figurative plot associationsparallels; musical markers: Chio-Chio-san’s aria “Un bel dì, vedremo” – like a sound trace of the main character; the voice of Maria Callas, woven into the canvas of the text as another means of intermediacy; a detailed description of the performance of the opera, covering the key moments of its drama (characterized by a deep reading of the musical series, in particular – its genre and intonation genesis). Opera by G. Puccini is presented as an extremely important semantic and compositional core of the novel.